Pelatihan Penyembeliahan Hewan Qurban Pada Takmir Masjid Guna Penyediaan Daging Aman, Sehat, Utuh dan Halal (ASUH) - Suwarno; Wiwik Misaco Yuniarti; Trilas Sardjito; M. Anam Al Arif; Supriyadi (Forum Kerjasama Pendidikan Tinggi, 2025)
Meat from qurban animals that are slaughtered halal and true, safe and common and decent for human consumption, will produce a taste of high quality. Meat may contain chemical residues, microbial contamination, and hazardous elements (hazard) that are harmful and disruptive to human health, so it is said that meat is a potentially hazardous food ingredient (potentially dangerous food = PHF). The purpose of this community service is to sacrifice qurban animals for takmirs of Surabaya City Mosque to provide